Fetishism and Sexual Objectification towards African (Black) Women in Modern Society: Analyzing the Portrayal of African Women in the Media - Fransisca Bianca (Jurnal Sentris, 2017)
In the perspective of multicultural feminism, beside society needs to end the subordination of women to men, it also needs to end the subordination of women to fellow women depending on her race, religion, education, etc. Multicultural feminism also emphasizes the acknowledgement of the difference between each woman’s background to understand their issues. Even so, the fact remains that women of color; African women in the case of this paper, still face objectification by society. While considered as possessing the ideal physique to fit men’s sexual desires, African women are still considered subordinate than Caucasian women. This does not only emphasize the portrayal of women as objects to men, but also emphasizes the consideration of women of color being in lower class than Caucasian women. Thus, with consideration to the way African women are portrayed in the media as exemplified by the case analysis in this paper, it could be concluded that African women (and other women of color) are still more often objectified in modern society.